2020
DOI: 10.1159/000511386
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Vasculitis Secondary to Durvalumab

Abstract: Ocular manifestations are very rarely reported as side effects to checkpoint inhibitors. We present a case of a 64-year-old Caucasian man in treatment with durvalumab for non-small-cell lung carcinoma who presented a retinal vasculitis with macular edema. After

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Avelumab and durvalumab are PD-L1 inhibitors commonly used in bladder cancer [77]. Ocular side effects are less common with PD-L1 inhibitors, compared to PD-1 inhibitors [80,82]. In fewer than 1% of cases, avelumab and durvalumab are associated with uveitis and iritis.…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Avelumab and durvalumab are PD-L1 inhibitors commonly used in bladder cancer [77]. Ocular side effects are less common with PD-L1 inhibitors, compared to PD-1 inhibitors [80,82]. In fewer than 1% of cases, avelumab and durvalumab are associated with uveitis and iritis.…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…In fewer than 1% of cases, avelumab and durvalumab are associated with uveitis and iritis. Durvalumab has also been linked to keratitis, while Andrade et al reported a case of durvalumab-induced retinal vasculitis [80,82].…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%